science anatomy
 👍
 👎
 👁
Respond to this Question
Similar Questions

math
Consider the sequence of steps to solve the equation: 5(x  3) = 7x 2 Step 1 ⇒ 10(x  3) = 7x Step 2 ⇒ 10x  30 = 7x Step 3 ⇒ 3x  30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

Physics
Water flows through a garden hose that goes up a step 20.0 cm high. The cross sectional area of the hose on top of the step is half that at the bottom of the step. If the water pressure is 143 kPa at the bottom of the step, and

chemistry
What is the percent ionization of a 1.38 mol/L weak acid if its Ka = 2.7 x 106? Answer to two (2) decimal places. I know what steps to use but have difficulty applying them to the quesiton Can someone please complete the question

Math
Use inverse operations to solve each equation. Explain each step and identify the property to reach step 19 = h/3  8 Solve the equation. Explain each step and identify the property used to reach step. 0.6x + 0.8 = 1.4

Algebra
Josephine solved a quadratic equation: (x+6)^2=49. Her work is shown below. Step 1: √(x+6)^2 = √49 Step 2: x+6 = 7 Step 3: x = 7−6 Step 4: x = 1 In which step did Josephine make an error? A step 4 B step 1 C step 2 D

ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? Step 1: (2x+3= x18 Step 2: 2x3=x18 Step 3: 3=3x18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

math
Omar wanted to know if x−5 is a factor of the polynomial p(x)=x3−6x2−x+30. He applied the Factor Theorem and concluded that x−5 is a factor of p(x), as shown in the following work. Step 1: p(5)=53−6(52)−5+30 Step 2:

physics
A 1.8 kg object is pulled along the floor with a force of 7.0 N acting horizontally. If the object accelerates at 2.4m/s^2, how much kinetic friction is acting? how do i do this? could you please explain step by step

algebra
write a function rule for the table. y= x 10, 7, 2, 6, 10 y 25, 19, 9, 7, 15 Can someone please show me step by step how to work this problem out step by step, I am so confused.

Math (Check 2 answers please)
1. What is the value of b in the equation b + 8 = 13? A. 5**** B. 8 C. 13 D. 21 2. The steps below show the incomplete solution to find the value of x for the equation 7x − 3x − 4 = −1 + 21: Step 1: 7x − 3x − 4 = −1 +

Help PLZ!!
consider the steps to simplify the expression. Which property is used to reach Step 3? Expression: 4 3 7 + 7 + (3 4 7 ) Step 1: = 4 3 7 + (3 4 7 ) + 7 Step 2: = 4 + ( 3 7 ) + (3) + ( 4 7 ) + 7 Step 3: = 4 + ( 3 7 ) + (
You can view more similar questions or ask a new question.